Preparation and application of organic / inorganic nano hybrid solid electrolyte based on fluorine-containing side group ionic liquid

By using the organic/inorganic nano -hybrid solid electrolytes based on the fluorine -side -based ionic liquid in the electrochemical device, the existing electrolyte is solved by the solubility of lithium salt, precipitation, and unstable electrode interface. And electrochemical stability has improved the performance and reliability of electrochemical devices.

CN119381523APending Publication Date: 2025-01-28DONGHUA UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411453882.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The existing polymer electrolytes have problems such as limited solubility of lithium salts, precipitation of lithium salts, and unstable electrode interfaces in electrochemical devices, resulting in a decrease in the performance and stability of electrochemical devices.

Method used

Adopt organic/inorganic nano -hybrid solid electrolyte based on fluorine -containing base ionic liquids. By mixing the fluorine -containing base ionic liquid, inorganic oxide nanoparticles, and polymer matrix Formed, an electrolyte with high electrical and electrochemical stability is prepared.

Benefits of technology

This electrolyte shows excellent conductivity and electrochemical stability in electrochemical devices, improves the performance and stability of the device, enhances the combination of interface with other components to ensure specialty It can still work stably under operation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119381523A_ABST
    Figure CN119381523A_ABST
Patent Text Reader

Abstract

The invention relates to preparation and application of an organic / inorganic nano hybrid solid electrolyte based on fluorine-containing side group ionic liquid. The electrolyte comprises the fluorine-containing side group ionic liquid, inorganic oxide nanoparticles and a polymer matrix. In the electrolyte prepared by the invention, the fluorine-containing side group ionic liquid not only provides excellent conductivity, but also enhances the electrochemical stability of the electrolyte. The addition of the inorganic oxide nanoparticles not only enhances the mechanical properties of the electrolyte, but also helps to improve the color rendering characteristic of the device. The polymer matrix serving as the polymer matrix of the electrolyte has excellent flexibility and plasticity, so that the electrolyte can adapt to devices with various shapes and structures.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of electrochemistry, and particularly relates to the preparation and application of an organic / inorganic nano-hybrid solid electrolyte based on fluorine-containing side-group ionic liquid. Background Art

[0002] Electrochemical devices are a type of equipment that uses electrochemical reactions to achieve energy conversion or storage, in which electrolytes are one of the key components. Electrolytes play a vital role in electrochemical devices, and their performance directly affects the efficiency, stability, and reliability of the devices. One of the goals of studying electrolytes is to find materials with high ionic conductivity and chemical stability to improve the performance of electrochemical devices. In addition, current research hotspots include the design and synthesis of new electrolytes, covering a wide range of fields from organic liquids to polymer-based solid electrolytes.

[0003] Polymer electrolytes are a type of electrolyte widely used in electrochemical devices. Their main characteristics are high flexibility, plasticity and good ion conductivity. In addition, the good adhesion between the polymer solid electrolyte and the device interface has a positive impact on the performance of electrochemical devices in many aspects. This strong adhesion can improve the stability of electrochemical devices, reduce interface resistance, improve cycle stability, increase the mechanical strength of polymer electrolytes, and improve safety.

[0004] Commonly used polymer electrolytes are composed of polymer matrix and lithium salt, which have problems such as limited lithium salt solubility, lithium salt precipitation, and unstable electrode interface. This will reduce the performance and stability of electrochemical devices, and safety and cost also need to be considered. Therefore, researchers are working hard to find new combinations of polymers and ionic liquids to overcome these problems and improve the performance and sustainability of electrochemical devices. Summary of the invention

[0005] In view of the defects of the prior art, the technical problem to be solved by the present invention is to provide a preparation and application of an organic / inorganic nano-hybrid solid electrolyte based on fluorine-containing side group ionic liquid. Many problems of electrolytes due to the presence of lithium salts are overcome. Thanks to the introduction of fluorine-containing side group ionic liquids, the electrolyte is provided with excellent conductivity and electrochemical stability, meeting the high performance requirements of electrolytes in electrochemical devices. At the same time, the addition of inorganic oxides improves the mechanical properties and color rendering characteristics. Thermoplastic polyurethane gives the electrolyte flexibility and plasticity, making it adaptable to various device shapes. High adhesion enhances the interfacial bonding with other components, improves the reliability of the overall device, and can still work stably under special operations such as bending, shearing, and extrusion.

[0006] The invention provides an organic / inorganic nano hybrid solid electrolyte. The electrolyte components include: fluorine-containing side group ionic liquid, inorganic oxide nano particles and a polymer matrix.

[0007] Preferably, the content of the fluorine-containing side group ionic liquid is 10-90wt.% of the total mass of the electrolyte; the content of the inorganic oxide nanoparticles is 0.1-5wt.% of the total mass of the electrolyte; the content of the polymer matrix is ​​10-90wt.% of the total mass of the electrolyte;

[0008] Further preferably, the content of the fluorine-containing side group ionic liquid is 40-80wt.% of the total mass of the electrolyte; the content of the inorganic oxide nanoparticles is 1-3wt.% of the total mass of the electrolyte; and the content of the polymer matrix is ​​20-60wt.% of the total mass of the electrolyte.

[0009] Preferably, the fluorinated side group ionic liquid is an imidazolyl-containing ionic liquid, wherein the side group (R1) at one end of the imidazolyl cation is one or more of ethyl, propyl, and butyl; the side group (R2) at the other end is one or more of 3-(3,3,4,4,4-pentafluorobutyl)-, 3-(1,1,1,2,2-pentafluoropropyl)-, 3-(1,1,1,2,2-pentafluoropentyl)-, 3-(1,1,1,2,2-pentafluorohexyl)-, 3-(1,1,1,2,2,3,3,4,4,5,5,6,6-tridecafluorooctyl)-; the anion X - Trifluoromethanesulfonimide (TFSI - ), hexafluorophosphate (PF6 - ), perchlorate (ClO4 - ), tetrafluoroborate (BF4 - ) one or more of the ions;

[0010] The structural formula of the fluorine-containing side group ionic liquid is: wherein R1 is one or more of ethyl, propyl, and butyl; R2 is one or more of 3-(3,3,4,4,4-pentafluorobutyl)-, 3-(1,1,1,2,2-pentafluoropropyl)-, 3-(1,1,1,2,2-pentafluoropentyl)-, 3-(1,1,1,2,2-pentafluorohexyl)-, and 3-(1,1,1,2,2,3,3,4,4,5,5,6,6-tridecafluorooctyl)-; and X - Trifluoromethanesulfonimide (TFSI - ), hexafluorophosphate (PF6 - ), perchlorate (ClO4 - ), tetrafluoroborate (BF4 - ) ions.

[0011] Further preferably, the fluorine-containing side group ionic liquid includes at least one of 3-(1,1,1,2,2-pentafluorohexyl)-1-ethylimidazole trifluoromethanesulfonyl imide, 3-(3,3,4,4,4-pentafluorobutyl)-1-ethylimidazole trifluoromethanesulfonyl imide, and 3-(1,1,1,2,2,3,3,4,4,5,5,6,6-tridecafluorooctyl)-1-ethylimidazole trifluoromethanesulfonyl imide.

[0012] The preparation method of the fluorine-containing side group ionic liquid comprises: The solvent is mixed, heated to 60-120°C under the protection of an inert gas, and a nucleophilic substitution reaction is carried out, and then an anion salt is added, washed, and dried to obtain a fluorinated side group ionic liquid. Wherein R1 is one or more of ethyl, propyl, and butyl; wherein the solvent is toluene; and the anion in the anion salt is trifluoromethanesulfonimide (TFSI - ), hexafluorophosphate (PF6 - ), perchlorate (ClO4 - ), tetrafluoroborate (BF4 - ) one or more of the following.

[0013] Preferably, the inorganic oxide nanoparticles include one or more of titanium dioxide TiO2, silicon dioxide SiO2, zirconium oxide ZrO2, aluminum oxide Al2O3, lithium aluminum oxide LiAlO2, and lithium silicon oxide Li4SiO4;

[0014] Furthermore, the particle size of the inorganic oxide nanoparticles is 10-100 nm.

[0015] Preferably, the polymer matrix includes one or more of polyethylene oxide PEO, polyvinylidene fluoride PVDF, polyvinylidene fluoride-propylene fluoride PVDF-HFP, polyvinylidene fluoride-trifluoroethylene PVDF-TrFE, polyacrylonitrile PAN, polymethyl methacrylate PMMA, polyester type, polyether type polyurethane PU.

[0016] The present invention provides a method for preparing any of the organic / inorganic nano-hybrid solid electrolytes, comprising:

[0017] (1) weighing each component according to a ratio, mixing a fluorine-containing side group ionic liquid, inorganic oxide nanoparticles and a polymer matrix to obtain a mixture of an organic / inorganic nano-hybrid solid electrolyte;

[0018] (2) placing the mixture in a high-temperature oven for preforming treatment to obtain an organic / inorganic nano-hybrid solid electrolyte containing a fluorine-containing side-group ionic liquid.

[0019] In step (1), the fluorine-containing side group ionic liquid, inorganic oxide nanoparticles and polymer matrix are fully and evenly mixed in different proportions by a mechanical stirrer to obtain a mixture of organic / inorganic nano hybrid solid electrolyte. The key to this step is to ensure that the mixing is fully uniform to ensure that the final product has ideal performance and structure.

[0020] Preferably, the mixture in step (1) is in a paste state.

[0021] Preferably, in step (1), the content of the fluorine-containing side group ionic liquid is 10-90 wt.% of the total mass of the electrolyte; the content of the inorganic oxide nanoparticles is 0.1-5 wt.% of the total mass of the electrolyte; and the content of the polymer matrix is ​​10-90 wt.% of the total mass of the electrolyte.

[0022] Further preferably, the content of the fluorine-containing side group ionic liquid is 40-80 wt.% of the total mass of the electrolyte; the content of the inorganic oxide nanoparticles is 1-3 wt.% of the total mass of the electrolyte; and the content of the polymer matrix is ​​20-60 wt.% of the total mass of the electrolyte.

[0023] Preferably, the preforming temperature in step (2) is 100-200°C.

[0024] More preferably, the preforming temperature in step (2) is 120-140°C.

[0025] The organic / inorganic nano-hybrid solid electrolyte obtained in step (2) is pressed and molded at high temperature by a hot press to obtain an electrolyte membrane with uniform thickness.

[0026] Furthermore, the thickness is controlled by multiple hot pressing with a mold to fix the thickness and expel the existing bubbles.

[0027] Preferably, the pressing molding temperature is 120-200° C.; and the fixed thickness is 0.1-5 mm.

[0028] More preferably, the pressing molding temperature is 120-140° C.; and the fixed thickness is 0.2-2 mm.

[0029] The present invention provides a dual-band electrochromic device (a carbon material dual-band electrochromic device based on an organic / inorganic nano-hybrid solid electrolyte of a fluorine-containing side-group ionic liquid), the device comprising the organic / inorganic nano-hybrid solid electrolyte and an electrode containing a carbon material.

[0030] Preferably, the organic / inorganic nano-hybrid solid electrolyte is disposed inside the two-layer carbonaceous material electrode, wherein the thickness of the organic / inorganic nano-hybrid solid electrolyte is uniform;

[0031] Preferably, the electrode of the carbon-containing material is a polyethylene PE electrode of the carbon-containing material;

[0032] Preferably, the carbon material includes one or more of graphene, activated carbon material, polythiophene polymer, single-walled carbon nanotube, and multi-walled carbon nanotube;

[0033] Preferably, the dual-band electrochromic device has a thickness of 0.5 to 2 mm.

[0034] The invention provides a method for preparing a dual-band electrochromic device, comprising: placing the organic / inorganic nano hybrid solid electrolyte inside two layers of carbonaceous material electrodes, and then placing the electrodes on a hot press for hot pressing.

[0035] Furthermore, a uniform thickness of organic / inorganic nano-hybrid solid electrolyte is coated on a polyethylene (PE) electrode containing carbon material and covered with another layer of polyethylene (PE) electrode containing carbon material, and the electrolyte is ensured to be in contact with one side of the carbon material electrode. The electrolyte is heat-pressed on a hot press and ensured to maintain good interface contact with the carbon material electrode.

[0036] Preferably, the carbon-containing material electrode is a polyethylene PE electrode made of carbon-containing material; the hot pressing molding temperature is 50 to 100° C., and the duration is 10 seconds to 5 minutes.

[0037] More preferably, the hot pressing temperature is 60-80° C. and the duration is 30 s-2 min.

[0038] The present invention provides an application of the organic / inorganic nano-hybrid solid electrolyte in the field of electrochemical devices, such as secondary batteries, electrochromic devices, wearable devices and other electrochemical devices.

[0039] The present invention includes: the preparation of an organic / inorganic nano-hybrid solid electrolyte based on a fluorine-containing side-group ionic liquid and the assembly of a carbon material dual-band electrochromic device. First, the fluorine-containing side-group ionic liquid, inorganic oxide nanoparticles and a polymer matrix are fully and evenly mixed in different proportions through a mechanical stirrer to obtain a mixture of an organic / inorganic nano-hybrid solid electrolyte. Subsequently, the electrolyte mixture is placed in a high-temperature oven for preforming treatment to obtain an organic / inorganic nano-hybrid solid electrolyte of a fluorine-containing side-group ionic liquid. Afterwards, the organic / inorganic nano-hybrid solid electrolyte of a fluorine-containing side-group ionic liquid is pressed and molded at high temperature by a hot press to obtain an electrolyte membrane with uniform thickness. Finally, the organic / inorganic nano-hybrid solid electrolyte with uniform thickness is placed inside a two-layer polyethylene electrode containing carbon material, and then placed on a hot press for hot pressing and molding, so that an organic / inorganic nano-hybrid solid electrolyte based on a fluorine-containing side-group ionic liquid and a carbon material dual-band electrochromic device can be obtained.

[0040] In the electrolyte prepared by the present invention, the fluorine-containing side group ionic liquid not only provides excellent conductivity, but also enhances the electrochemical stability of the electrolyte. The addition of inorganic oxide nanoparticles not only enhances the mechanical properties of the electrolyte, but also helps to improve the color rendering characteristics of the device. The polymer matrix, as a polymer matrix of the electrolyte, has excellent flexibility and plasticity, allowing the electrolyte to adapt to devices of various shapes and structures. In addition, the high adhesion of the electrolyte also enhances the interfacial bonding force with other components, thereby improving the reliability of the overall device, and can still work stably under special operations such as bending, shearing, and extrusion. This gives it a wide range of application prospects in the fields of secondary batteries, electrochromic, wearable devices, etc.

[0041] Beneficial Effects

[0042] (1) The present invention adopts a simple and reliable preparation method to meet the large-scale production needs of organic / inorganic nano-hybrid solid electrolytes based on fluorine-containing side group ionic liquids;

[0043] (2) The organic / inorganic nano-hybrid solid electrolyte based on fluorine-containing side group ionic liquid prepared by the present invention overcomes the problems of easy leakage of liquid electrolyte and low ionic conductivity of all-solid electrolyte. The unique design and addition of fluorine-containing side group ionic liquid ensure that the electrolyte has high electrochemical stability and meets the requirements of high-performance electrochemical devices. The improved water vapor insensitivity meets the stable operation of electrochemical devices in complex application environments.

[0044] (3) The present invention effectively improves the ionic conductivity and mechanical stability of the organic / inorganic nano-hybrid solid electrolyte containing fluorine-containing side-group ionic liquid by controlling the amount and type of the fluorine-containing side-group ionic liquid, the amount and type of the inorganic oxide nanoparticles, and the amount and type of the polymer matrix, thereby meeting the requirements of efficient operation of electrochemical devices in actual use and processability in the production process;

[0045] (4) The organic / inorganic nano-hybrid solid electrolyte based on fluorine-containing side-group ionic liquid prepared by the present invention has excellent flexibility and plasticity, adapts to the requirements of the shape of each device, and ensures the improvement of the overall device reliability. It can still maintain stable operation even under special operations such as bending, shearing, and extrusion. These characteristics make it have broad application prospects in the fields of secondary batteries, electrochromic, wearable devices, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] Figure 1 is the structural formula of fluorine-containing side group ionic liquid;

[0047] Figure 2 Reaction scheme for preparing fluorine-containing side group ionic liquid in Example 1;

[0048] Figure 3 Preparation of 3-(1,1,1,2,2,3,3,4,4,5,5,6,6-tridecafluorooctyl)-1-ethylimidazole trifluoromethanesulfonimide in Example 1 1 H NMR spectrum;

[0049] Figure 4 The organic / inorganic nano-hybrid solid electrolyte based on fluorine-containing side group ionic liquid prepared in Example 1;

[0050] Figure 5 Electrochemical impedance spectroscopy of the organic / inorganic nanohybrid solid electrolyte based on fluorine-containing side group ionic liquid prepared in Example 1;

[0051] Figure 6 Linear sweep voltammetry spectrum of the organic / inorganic nanohybrid solid electrolyte based on fluorine-containing side group ionic liquid prepared in Example 1;

[0052] Figure 7 Electrochemical impedance spectroscopy of the organic / inorganic nanohybrid solid electrolyte based on fluorine-containing side group ionic liquid prepared in Example 2;

[0053] Figure 8 Linear sweep voltammetry spectrum of the organic / inorganic nanohybrid solid electrolyte based on fluorine-containing side group ionic liquid prepared in Example 2;

[0054] Fig. 9 CIE LAB color space value of the organic / inorganic nano-hybrid solid electrolyte based on fluorine-containing side group ionic liquid prepared in Example 2;

[0055] Fig.10 Electrochemical impedance spectroscopy of the organic / inorganic nanohybrid solid electrolyte based on fluorine-containing side group ionic liquid prepared in Example 3;

[0056] Fig.11 Linear sweep voltammetry spectrum of the organic / inorganic nanohybrid solid electrolyte based on fluorine-containing side group ionic liquid prepared in Example 3;

[0057] Fig.12 CIE LAB color space value of the organic / inorganic nano-hybrid solid electrolyte based on fluorine-containing side group ionic liquid prepared in Example 3;

[0058] Fig.13 Digital photo of carbon material dual-band electrochromic device based on organic / inorganic nano-hybrid solid electrolyte of fluorine-containing side group ionic liquid prepared in Example 3;

[0059] Fig.14The coloring and fading CIE LAB color space value of the carbon material dual-band electrochromic device based on the organic / inorganic nano-hybrid solid electrolyte of the fluorine-containing side group ionic liquid prepared in Example 3;

[0060] Fig.15 The temperature regulating performance of the carbon material dual-band electrochromic device based on the organic / inorganic nano-hybrid solid electrolyte of the fluorine-containing side group ionic liquid prepared in Example 3;

[0061] Fig.16 Electrochemical impedance spectroscopy of the organic / inorganic nanohybrid solid electrolyte based on fluorine-containing side group ionic liquid prepared in Example 4;

[0062] Fig.17 Linear sweep voltammetry spectrum of the organic / inorganic nanohybrid solid electrolyte based on fluorine-containing side group ionic liquid prepared in Example 4. DETAILED DESCRIPTION

[0063] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0064] The fluorine-containing side group ionic liquid is an imidazolyl ionic liquid, and its structural schematic diagram is as follows Figure 1 As shown. Wherein, the side group (R1) at one end of the imidazolium cation is one or more of ethyl, propyl, and butyl; the side group (R2) at the other end is one or more of 3-(3,3,4,4,4-pentafluorobutyl)-, 3-(1,1,1,2,2-pentafluoropropyl)-, 3-(1,1,1,2,2-pentafluoropentyl)-, 3-(1,1,1,2,2-pentafluorohexyl)-, 3-(1,1,1,2,2,3,3,4,4,5,5,6,6-tridecafluorooctyl)-; the anion X - Trifluoromethanesulfonimide (TFSI - ), hexafluorophosphate (PF6 - ), perchlorate (ClO4 - ), tetrafluoroborate (BF4 - )ion.

[0065] Titanium dioxide (TiO2), silicon dioxide (SiO2), zirconium oxide (ZrO2), aluminum oxide (Al2O3), lithium aluminum oxide (LiAlO2) and lithium silicon oxide (Li4SiO4) were purchased from Aladdin. Polyethylene oxide (PEO), polyvinylidene fluoride (PVDF), polyvinylidene fluoride-propylene fluoride (PVDF-HFP), polyvinylidene fluoride-trifluoroethylene (PVDF-TrFE), polyacrylonitrile (PAN), polymethyl methacrylate (PMMA), polyester or polyether polyurethane (PU) were purchased from MacLean.

[0066] The UV-visible transmission spectrum was measured by a UV-visible spectrophotometer model U-T6 from Yipu Instrument Manufacturing (Shanghai) Co., Ltd. The electrochemical impedance spectroscopy (EIS), linear sweep voltammetry (LSV) and chronoamperometry (CA) were measured using a VSP-300 electrochemical workstation model from Biologic SAS, France.

[0067] Example 1

[0068] The method for preparing an organic / inorganic nano-hybrid solid electrolyte based on a fluorine-containing side group ionic liquid of the present invention comprises:

[0069] (1) Preparation method and route of fluorinated side group ionic liquid. Specifically, 10 g of 1-ethylimidazole and 20 mL of toluene were added to a clean three-necked flask and placed in an oil bath, and heated under the protection of argon gas, and then 1,1,1,2,2,3,3,4,4,5,5,6,6-tridecafluoro-8-iodooctane was refluxed at 100°C, and the reaction was terminated after 48 hours and cooled to room temperature. Then, the unreacted raw materials on the upper layer were removed, and the viscous liquid on the lower layer was precipitated into a large amount of ether solvent, and the precipitate was repeatedly washed and collected under stirring. Finally, the precipitate was dried in a vacuum oven at 60°C for 24 hours to remove the organic solvent.

[0070] (2) 10 g of the above product was dissolved in 50 mL of deionized water, and then an excess of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) was added to the solution, and then the precipitated solution was washed and collected with a large amount of deionized water. Finally, the solution was dried in a vacuum oven at 60° C. for 24 hours to remove the deionized water, thereby obtaining the desired 3-(1,1,1,2,2,3,3,4,4,5,5,6,6-tridecafluorooctyl)-1-ethylimidazole trifluoromethanesulfonyl imide.

[0071] (3) 4 g of 3-(1,1,1,2,2,3,3,4,4,5,5,6,6-tridecafluorooctyl)-1-ethylimidazole trifluoromethanesulfonyl imide, 0.1 g of titanium dioxide (TiO2) (D50 particle size: 20 nm) nanoparticles and 6 g of polyvinylidene fluoride-propylene fluoride (PVDF-HFP) were fully and uniformly mixed by a mechanical stirrer to obtain a mixture of an organic / inorganic nano-hybrid solid electrolyte.

[0072] (4) placing the electrolyte mixture in a high-temperature oven at 120° C. for preforming treatment to obtain an organic / inorganic nano-hybrid solid electrolyte containing a fluorine-containing side-group ionic liquid.

[0073] (5) The organic / inorganic nano-hybrid solid electrolyte of the fluorine-containing side group ionic liquid is fixed to a thickness of 0.2 mm and is pressed and molded at a high temperature of 120° C. by a hot press to obtain an electrolyte membrane with uniform thickness.

[0074] The organic / inorganic nano-hybrid solid electrolyte based on fluorine-containing side group ionic liquid prepared in Example 1 is as follows Figure 2 As shown in Figure 2, fluorinated side group ionic liquids are prepared by nucleophilic substitution reaction. Figure 3 As shown, the 1H NMR spectrum of 3-(1,1,1,2,2,3,3,4,4,5,5,6,6-tridecafluorooctyl)-1-ethylimidazole trifluoromethanesulfonimide. Figure 4 As shown in the figure, a large-area solid electrolyte with uniform thickness can be produced through a simple molding process, and the solid electrolyte also has a certain flexibility and still maintains high flexibility at a large bending angle. Figure 5 As shown in the electrochemical impedance spectroscopy test of the electrolyte placed in a stainless steel double inert electrode, the ionic conductivity of the organic / inorganic nanohybrid solid electrolyte based on fluorinated side group ionic liquid reached 8.1×10 -5 S cm -1 This indicates that the electrolyte can meet the requirements of most electrochemical devices. Figure 6 As shown in the figure, the electrolyte is placed in the linear sweep voltammetry spectrum tested in stainless steel inert and single-walled carbon nanotube electrodes. The organic / inorganic nanohybrid solid electrolyte based on fluorinated side-group ionic liquid has an electrochemical withstand voltage window of 4.5 V under the test conditions of inert electrodes. The solid electrolyte operates stably in usage scenarios such as bending.

[0075] Example 2

[0076] The method for preparing an organic / inorganic nano-hybrid solid electrolyte based on a fluorine-containing side group ionic liquid of the present invention comprises:

[0077] (1) 6 g of 3-(1,1,1,2,2,3,3,4,4,5,5,6,6-tridecafluorooctyl)-1-ethylimidazole trifluoromethanesulfonyl imide, 0.2 g of aluminum oxide (Al2O3) (D50 particle size: 25 nm) particles and 4 g of polyester polyurethane (PU) were mixed uniformly by a mechanical stirrer to obtain a mixture of an organic / inorganic nano-hybrid solid electrolyte.

[0078] (2) placing the electrolyte mixture in a high-temperature oven at 140° C. for preforming treatment to obtain an organic / inorganic nano-hybrid solid electrolyte containing a fluorine-containing side-group ionic liquid.

[0079] (3) The organic / inorganic nano-hybrid solid electrolyte of the fluorine-containing side group ionic liquid is fixed to a thickness of 0.5 mm and is pressed and molded at a high temperature of 130° C. by a hot press to obtain an electrolyte membrane with uniform thickness.

[0080] (4) An organic / inorganic nano-hybrid solid electrolyte with uniform thickness is placed inside two layers of polyethylene (PE) electrodes containing carbon materials, which are then placed on a hot press at 60°C for hot pressing.

[0081] The AC impedance spectrum of the organic / inorganic nanohybrid solid electrolyte based on fluorinated side group ionic liquid was tested in a stainless steel double inert electrode. Figure 7 As shown, the ionic conductivity of the solid electrolyte reached 1.18×10 -4 S cm -1 .like Figure 8 As shown in Figure 1, the electrolyte was placed in a stainless steel inert and single-walled carbon nanotube electrode to test the linear sweep voltammetry spectrum, and the electrochemical voltage window of the organic / inorganic nanohybrid solid electrolyte based on fluorine-containing side group ionic liquid reached 4.8V. Fig. 9 As shown, the chromaticity of the organic / inorganic nanohybrid solid electrolyte based on fluorine-containing side group ionic liquid is Lab = [94.48, -1.09, 1.07], which is close to pure white.

[0082] Solid-state electrolytes operate stably in usage scenarios such as bending.

[0083] Example 3

[0084] The method for preparing an organic / inorganic nano-hybrid solid electrolyte based on a fluorine-containing side group ionic liquid of the present invention comprises:

[0085] (1) 6 g of 3-(1,1,1,2,2,3,3,4,4,5,5,6,6-tridecafluorooctyl)-1-ethylimidazole trifluoromethanesulfonyl imide, 0.5 g of titanium dioxide (TiO2) (D50 particle size: 20 nm) particles and 4 g of polyester polyurethane (PU) were mixed thoroughly and uniformly by a mechanical stirrer to obtain a mixture of an organic / inorganic nano-hybrid solid electrolyte.

[0086] (2) placing the electrolyte mixture in a high-temperature oven at 140° C. for preforming treatment to obtain an organic / inorganic nano-hybrid solid electrolyte containing a fluorine-containing side-group ionic liquid.

[0087] (3) The organic / inorganic nano-hybrid solid electrolyte of the fluorine-containing side group ionic liquid is fixed to a thickness of 0.5 mm and is pressed and molded at a high temperature of 130° C. by a hot press to obtain an electrolyte membrane with uniform thickness.

[0088] (4) An organic / inorganic nano-hybrid solid electrolyte with uniform thickness is placed inside two layers of polyethylene (PE) electrodes containing single-walled carbon tubes, which are then placed on a hot press at 60°C for hot pressing.

[0089] The AC impedance spectrum of the organic / inorganic nanohybrid solid electrolyte based on fluorinated side group ionic liquid was tested in a stainless steel double inert electrode. Fig.10 As shown, the ionic conductivity of the solid electrolyte reached 1.41×10 -4 S cm -1 .like Fig.11 As shown in the linear sweep voltammetry spectrum of the electrolyte placed in the stainless steel inert electrode and the single-walled carbon nanotube electrode, the electrochemical voltage window of the organic / inorganic nanohybrid solid electrolyte based on the fluorine-containing side group ionic liquid in the inert electrode reached 4.6V. Fig.12 As shown, the CIELAB color space value of the organic / inorganic nanohybrid solid electrolyte based on fluorinated side group ionic liquid is [96.52, -0.62, 1.48], which is close to pure white.

[0090] like Fig.13 The figure shows a 8×8 cm single-walled carbon tube dual-band electrochromic device based on an organic / inorganic nano-hybrid solid electrolyte with fluorinated side-group ionic liquid. At a voltage of 4.5 V, the color of the device can be switched from dark black to yellow-brown. Fig.14 As shown in FIG. 1 , the CIELAB color space value corresponding to the single-walled carbon tube dual-band electrochromic device based on the organic / inorganic nano-hybrid solid electrolyte of the fluorine-containing side group ionic liquid can change from [63.0, 2.6, 8.6] to [43.1, 11.0, 16.0]. Fig.15The temperature control test of the prepared device on a heating table at 50°C is shown. After applying a voltage of 4.5V, the temperature drops from 38°C to 33°C. The solid electrolyte operates stably in usage scenarios such as bending.

[0091] Example 4

[0092] The method for preparing an organic / inorganic nano-hybrid solid electrolyte based on a fluorine-containing side group ionic liquid of the present invention comprises:

[0093] (1) Preparation method and route of fluorinated side group ionic liquid. Specifically, 10 g of 1-ethylimidazole and 20 mL of toluene were added to a clean three-necked flask and placed in an oil bath, and heated under the protection of argon gas, and then 3,3,4,4,4-pentafluoro-bromobutane was refluxed at 90°C, and the reaction was terminated after 48 hours and cooled to room temperature. Then, the unreacted raw materials on the upper layer were removed, and the viscous liquid on the lower layer was precipitated into a large amount of ether solvent, and the precipitate was repeatedly washed and collected under stirring. Finally, the precipitate was dried in a vacuum oven at 60°C for 24 hours to remove the organic solvent.

[0094] (2) 10 g of the above product was dissolved in 50 mL of deionized water, and then an excess of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) was added to the solution, and then the precipitated solution was washed and collected with a large amount of deionized water. Finally, the solution was dried in a vacuum oven at 60° C. for 24 hours to remove the deionized water, thereby obtaining the desired 3-(3,3,4,4,4-pentafluorobutyl)-1-ethylimidazole trifluoromethanesulfonyl imide.

[0095] (3) 6 g of 3-(3,3,4,4,4-pentafluorobutyl)-1-ethylimidazole trifluoromethanesulfonyl imide, 0.5 g of titanium dioxide (TiO2) (D50 particle size: 20 nm) particles and 4 g of polyester polyurethane (PU) were mixed thoroughly and evenly by a mechanical stirrer to obtain a mixture of an organic / inorganic nano-hybrid solid electrolyte.

[0096] (4) placing the electrolyte mixture in a high-temperature oven at 140° C. for preforming treatment to obtain an organic / inorganic nano-hybrid solid electrolyte containing a fluorine-containing side-group ionic liquid.

[0097] (5) The organic / inorganic nano-hybrid solid electrolyte of the fluorine-containing side group ionic liquid is fixed to a thickness of 0.5 mm and is pressed and molded at a high temperature of 130° C. by a hot press to obtain an electrolyte membrane with uniform thickness.

[0098] (6) An organic / inorganic nano-hybrid solid electrolyte with uniform thickness is placed inside two layers of polyethylene (PE) electrodes containing single-walled carbon tubes, which are then placed on a hot press at 60°C for hot pressing.

[0099] The AC impedance spectrum of the organic / inorganic nanohybrid solid electrolyte based on 3-(3,3,4,4,4-pentafluorobutyl)-1-ethylimidazolium trifluoromethanesulfonyl imide was tested in a stainless steel double inert electrode. Fig.16 As shown, the ionic conductivity of the solid electrolyte reached 1.25×10 -4 S cm -1 .like Fig.17 As shown, the electrolyte was placed in a stainless steel inert and single-walled carbon nanotube electrode to test the linear sweep voltammetry spectrum, and the electrochemical withstand voltage window of the organic / inorganic nanohybrid solid electrolyte based on fluorine-containing side group ionic liquid reached 4.4 V. The solid electrolyte operates stably in usage scenarios such as bending.

Claims

1. An organic / inorganic nano-hybrid solid electrolyte, characterized in that: The electrolyte components include: fluorine-containing side group ionic liquid, inorganic oxide nanoparticles and a polymer matrix.

2. The electrolyte according to claim 1, characterized in that The content of the fluorine-containing side group ionic liquid is 10-90wt.% of the total mass of the electrolyte; the content of the inorganic oxide nanoparticles is 0.1-5wt.% of the total mass of the electrolyte; the content of the polymer matrix is ​​10-90wt.% of the total mass of the electrolyte; The fluorine-containing side group ionic liquid is an imidazolyl-containing ionic liquid, wherein the side group R1 at one end of the imidazolyl cation is one or more of ethyl, propyl, and butyl; the side group R2 at the other end is one or more of 3-(3,3,4,4,4-pentafluorobutyl)-, 3-(1,1,1,2,2-pentafluoropropyl)-, 3-(1,1,1,2,2-pentafluoropentyl)-, 3-(1,1,1,2,2-pentafluorohexyl)-, 3-(1,1,1,2,2,3,3,4,4,5,5,6,6-tridecafluorooctyl)-; the anion X - TFSI - , hexafluorophosphate PF6 - 、Perchlorate ClO4 - 、Tetrafluoroborate BF4 - One or more of the ions; The inorganic oxide nanoparticles include one or more of titanium dioxide TiO2, silicon dioxide SiO2, zirconium oxide ZrO2, aluminum oxide Al2O3, lithium aluminum oxide LiAlO2, and lithium silicon oxide Li4SiO4; The polymer matrix includes one or more of polyethylene oxide PEO, polyvinylidene fluoride PVDF, polyvinylidene fluoride-propylene fluoride PVDF-HFP, polyvinylidene fluoride-trifluoroethylene PVDF-TrFE, polyacrylonitrile PAN, polymethyl methacrylate PMMA, polyester type, polyether type polyurethane PU.

3. A method for preparing the organic / inorganic nano-hybrid solid electrolyte according to any one of 1-2, comprising: (1) weighing each component according to a ratio, mixing the fluorine-containing side group ionic liquid, the inorganic oxide nanoparticles and the polymer matrix to obtain a mixture; (2) The mixture is preformed to obtain an organic / inorganic nano-hybrid solid electrolyte.

4. The preparation method according to claim 3, characterized in that: The preforming temperature in step (2) is 100-200° C.; The organic / inorganic nano-hybrid solid electrolyte obtained in step (2) is pressed and molded to obtain an electrolyte membrane.

5. The preparation method according to claim 4, characterized in that: The pressing molding temperature is 120-200°C; The organic / inorganic nano hybrid solid electrolyte is placed in a mold with a fixed thickness and then pressed into shape; wherein the fixed thickness is 0.1 to 5 mm.

6. A dual-band electrochromic device, characterized in that: The device comprises the organic / inorganic nano-hybrid solid electrolyte according to any one of claims 1-2 and an electrode containing a carbon material.

7. The device according to claim 6, characterized in that: The organic / inorganic nano-hybrid solid electrolyte is arranged inside the two-layer carbon-containing material electrode, wherein the thickness of the organic / inorganic nano-hybrid solid electrolyte is uniform; The electrode containing carbon material is a polyethylene PE electrode containing carbon material; The carbon material includes one or more of graphene, activated carbon material, polythiophene polymer, single-walled carbon nanotube, and multi-walled carbon nanotube; The thickness of the dual-band electrochromic device is 0.5-2 mm.

8. A method for preparing a dual-band electrochromic device, comprising: The organic / inorganic nano-hybrid solid electrolyte according to claim 1 is placed inside two layers of carbon-containing material electrodes, followed by hot pressing.

9. The preparation method according to claim 8, characterized in that: The carbon-containing material electrode is a polyethylene PE electrode made of carbon-containing material; the hot pressing molding temperature is 50-100° C., and the duration is 10s-5min.

10. Use of the organic / inorganic nano-hybrid solid electrolyte according to claim 1 in the field of electrochemical devices.